2016
DOI: 10.1002/2016jd025352
|View full text |Cite
|
Sign up to set email alerts
|

Controlling factors of rainwater and water vapor isotopes at Bangalore, India: Constraints from observations in 2013 Indian monsoon

Abstract: Isotopic ratios of rainwaters are believed to decrease with the amount of rainfall. However, analyses of the isotopic composition of rainwater and water vapor samples collected from Bangalore during the monsoon period of 2013 fail to show any simple relationship with the local meteorological parameters whereas show good correlation with the regional integrated convective activity. The correlation is particularly high when the averaging is done over the preceding 8 to 15 days, showing the influence of mixing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 63 publications
4
15
0
Order By: Relevance
“…The calculated parameter F varied from 56 to 99% during the study period. The parameter f ( f = 1‐ F , the fraction of raindrop reevaporation water) ranged from 1 to 43%, with an average of 16.4 ± 12.9%, which was consistent with the previous studies (Rahul et al, ; Worden et al, ). Worden et al () reported that 20–50% of rainfall evaporation contributed significantly to lower troposphere humidity near convective clouds.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The calculated parameter F varied from 56 to 99% during the study period. The parameter f ( f = 1‐ F , the fraction of raindrop reevaporation water) ranged from 1 to 43%, with an average of 16.4 ± 12.9%, which was consistent with the previous studies (Rahul et al, ; Worden et al, ). Worden et al () reported that 20–50% of rainfall evaporation contributed significantly to lower troposphere humidity near convective clouds.…”
Section: Discussionsupporting
confidence: 91%
“…A significant negative relationship between the reevaporation faction and rainfall d-excess is shown in Figure 6 (r= -0.667, p <.001), which supports the aforementioned hypothesis that re-evaporation below cloud influences the isotopic composition of rainfall during the descent process. A previous study by Rahul et al (2016) also reported similar findings, with a low coefficient between the re-evaporation fraction and rainfall d-excess.…”
Section: Subcloud Reevaporation Processes Can Cause Low D-excess Valuessupporting
confidence: 79%
See 2 more Smart Citations
“…Atmospheric moisture, condensed inside the cold trap as ice, was allowed to melt at room temperature (≈ 15-20 • C) and then transferred into 5 ml polyethylene storage vials. ALl the samples were stored at 4 • C. A similar setup for water vapor sampling was presented in the earlier studies Rahul et al (2016Rahul et al ( , 2018.…”
mentioning
confidence: 99%